Stakeholder Satisfaction in Long Segment Maintenance Contract: Application to a Hills-Road Network - Rifai, Andri Irfan; Isradi, Muhammad; Prasetijo, Joewono; ., Herman; Mufhidin, Amar (International Journal of Membrane Science and Technology, 2023)
Hills-road network has an essential role in maintaining the flow of transportation and logistics in mountainous areas. Implementing the Long Segment Maintenance Contract (LSMC) is one step in producing better road services and performance. The success rate of PMS implementation can be seen from the road performance and the level of satisfaction of stakeholders consisting of owners, implementers, supervision consultants, and users. This research was conducted to determine stakeholders' level of interest and satisfaction in the implementation of LSMC in the mountain road network. The methods used are Importance Performance Analysis and Customer Satisfaction Index. As a case study, the hills road network in Cirebon-Kuningan-Ciamis, West Java, Indonesia, was chosen along 103.08 km. Questionnaires were distributed to all stakeholders in the implementation of LSCM in these sections. Data analysis was carried out on questionnaires obtained from the owner as many as three respondents, contractors four respondents, supervised seven respondents, and road users as many as 100 respondents. The results showed that, in general, the level of stakeholder importance was relatively high, with an average of 4.22, an average performance level of 3.70, and a CSI value of 86.9.% or very satisfactory. In comparison, road users' on-road performance is relatively high, with an average of 4.44 with, an average level of performance of 4.41, and a CSI value of 86.83%, or very satisfactory. Furthermore, the importance of road users' on-road response time is relatively high, with an average of 4.42, an average performance level of 4.41, and a CSI value of 86.09%, or very satisfactory. Attributes that greatly influence the opinion of road users and stakeholders on LSCM in the Hill Road Network are related to the control of runoff water and routine road maintenance.